ANALISIS PENGARUH INFLASI, JUMLAH UANG BEREDAR, DAN PRODUK DOMESTIK BRUTO TERHADAP RETURN ON ASSET (ROA) BANK SYARIAH DI INDONESIA - Riyanto, Ibnu Seyna; Asakdiyah, Salamatun (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to explain the analysis of the influence of inflation, amount of money supply and gross domestic product to return on assets (ROA) Islamic Banks in Indonesia for the period 2010-2014. Macroeconomic variables used in this research are inflation, the amount of money supply and gross domestic product. Indicators used to assess performance Islamic Bank finance in this study is Return On Assets (ROA). This research uses documentation method with secondary data obtained from the Bank Indonesia website, the Central Statistics Agency and the respective Bank's website. The sampling technique used in this study using a purposive sampling method, so the number of samples is used in this study amounted to 7 Islamic banks in Indonesia. Technique data analysis uses multiple linear regression analysis, classical assumption test and significance test. The results showed, partial inflation was not significant effect on Return On Assets (ROA). The money supply partially negative and significant effect on Return On Assets (ROA). Gross Domestic Product has a positive and significant effect on Return On Assets (ROA). Whereas simultaneously shows inflation, amount money supply and gross domestic product have a significant effect on Return On Assets (ROA).